Pemanfaatan Digital Marketing dalam Membangun Brand Awareness pada Mebel Sakinah Karawang - Husen, Aliyah; Nurlenawati, Netti; Triadinda, Dexi (J-MAS (Jurnal Manajemen dan Sains), 2024)
Research on Sakinah Furniture Karawang aims to find out how effective the impact is on the use of digital marketing, which is one of the strategies at Sakinah Furniture. This research is qualitative research that uses a descriptive approach. Researchers conducted direct observations and interviews with the owner of Sakinah Furniture, Mrs. Hj. Anne Barkah. Based on observations and interviews, direct information was obtained when observing the social media platforms being run and conducting in-depth interviews with the owners and loyal customers, Mrs. Dian and Mr. Eja, to conduct research. The results of interviews and research show that the use of digital marketing with the social media platform Instagram has had an impact on increasing the sales volume of mattresses by 60%, besides that it also has an impact on increasing the company's income. Sakinah Furniture has quality products, making this furniture Top Of Mind or at the top of consumers' minds when buying furniture products in Karawang Regency.